Peran Financial Management Behavior Sebagai Mediasi Fintech Dan Literasi Keuangan Terhadap Kinerja UMKM Kota Batam - Hikmah, Hikmah; Khoiri, M (Jurnal USAHA, 2024)
This study aims to analyze the effect of financial literacy and financial technology (fintech) on business performance mediated by financial management behavior. This study uses a quantitative research design using covariance-based partial least square (PLS).Data collection was carried out through distributing questionnaires online and offline to fintech users spread across the Batam City area, especially in Sagulung and Batu Aji sub-districts. By using the Jacob Cohen formula, the sample in this study was 204 respondents. The instrument used in the study was a questionnaire. The research shows the following results: First, fintech has a significant positive effect on business performance. Second, financial literacy also has a significant positive effect on business performance.  Third, financial management behavior has a significant positive effect on business performance.  Furthermore, the fourth and fifth hypotheses prove that fintech and financial literacy have a significant positive effect on financial management behavior.